Comparison of clinicopathologic findings and urine drug screen results in cannabis-positive and control dogs - Pereira, Helder Camilo da Silva; Barbosa, Wesley Marinho Brandão; Venceslau, Mariana Ferreira; Guerra, Ricardo Romão; Carvalho, Lucas Rannier Ribeiro Antonino (Frontiers in Veterinary Science, 2025)
IntroductionCannabis intoxication is increasingly reported in small animal practice, often resulting from accidental ingestion of human products or unsupervised access to the plant. Although clinical signs are well documented, laboratory alterations remain poorly described. This study aimed to confirm cannabis intoxication in dogs using a rapid urinary test for THC metabolites and to investigate associated hematological, biochemical, and urinary alterations.MethodsIn this study, nine dogs that were admitted to the emergency veterinary clinic in João Pessoa, Brazil, between 2021 and 2022, with suspected cannabis ingestion and owner confirmation, were evaluated. The animals were included regardless of breed, sex or age, and the results compared with healthy animals (control). Clinical signs were treated supportively. Urine and blood samples were collected 6 h after admission. Dogs were classified as “positive” or “negative/control” based on chromatographic detection of THC metabolites (PoCT COC/THC Assure Tech, Westlake Eco Zone/China; ANVISA 80885650015). Hematological analysis evaluated anemia, leukocyte, and platelet counts; serum biochemistry focused on hepatic and renal markers; urinalysis assessed color, clarity, specific gravity, and pH.ResultsNo statistically significant differences were observed between intoxicated and non-intoxicated dogs in any of the laboratory parameters. Additionally, most animals showed only discrete or absent clinical signs.DiscussionThese findings suggest that accidental cannabis ingestion in dogs tends to result in mild physiological effects and minimal laboratory alterations, indicating a low risk of severe toxicity. Nonetheless, accurate identification of exposure using diagnostic tools is essential for appropriate case management. A deeper understanding of the endocannabinoid system in companion animals is key to improving clinical decision-making and assessing potential risks associated with cannabis exposure.